John Steinbeck on set of, Full House - Unknown:::Creator::::::::::::
Steinbeck sitting a a desk filming the prologue to the O. Henry film, Full House, a 1952 American anthology film made by 20th Century Fox, consisting of five films, each based on a story by O. Henry. RESTRICTED USE